Eastern Shona : a comparative dialect study - Borland, C H (African Languages and Literatures, 2016)
In this paper, the speech patterns of eleven individuals living in the Eastern half of Rhodesia are described and compared. Each individual was selected as being representative of a number of localities described in the map below. The first part of the paper is concerned with the abstraction of comparable linguistic units from the dialects. These units are abstracted at various levels of analysis and unit categories include phonemes, tonemes, morphophonemes, tonomorphemes and morphemes. Each unit category is described in relation to the general structural framework of the dialects established by a sentence analysis. The units so abstracted and described constitute the distinctive attributes of each dialect. In part two the dialects are compared and classified by computer according to their correspondence to approximately one thousand selected properties.